Karakter Kuantitatif Melon Generasi S0-S4 - Siti Rohmatin; Kaswan Badami; Gita Pawana (Universitas Trunojoyo Madura, 2022)
One of the obstacles to melon cultivation is the availability of seeds and the high price of melon seeds. This condition causes the need to assemble superior melon varieties with the expected characters. This study aims to form a pure line of melon with certain superior characteristics and can be proposed as a new high-yielding variety in the open-pollinated category. The research was conducted at the Experimental Garden of the Agrotechnology Study Program, Faculty of Agriculture, Trunojoyo University, Madura, from September-December 2022. This study used a randomized block design method. The treatments used were nine pure lines of melon (PK-669, D-162, PK-361, PK-165, PK-114, D-029, D-5089, PK-211, and comparison). Each treatment was repeated three times, and each experimental unit consisted of 12 plants. Research data were analyzed using analysis of variance (ANOVA) and HSD test α = 0.05. The selection advancement was analyzed by comparing character data for each generation. The research showed that the results of the characterization of ten melon lines S0-S4 generation on the characters of fruit length, fruit diameter, flesh thickness, and melon fruit weight showed a decreasing trend in each generation. The S4 generation (9.17 °brix) in the character of the average sugar content there was an increase that was not significantly different from the S3 generation (9.03 °brix), while the number of seeds in each generation had an average value that was not significantly different but occurred an increase in the number of seeds in the S3 (372) and S4 (381) generations. An increase in one generation of the population in the linear regression equation is estimated to reduce the character of fruit length by 0.50 cm, fruit diameter by 0.465 cm, flesh thickness by 0.140 cm, fruit weight by 0.199 Kg, sugar content by 0.752 °brix, and a number of seeds by 5.4.